Answer:
![\textsf{i)}\quad \tan A + \tan B=(4√(3))/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/1vqtqsbh8s25bzwfmpziqiban8uqln0o4s.png)
![\textsf{ii)} \quad \sec A - \csc B=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/l3g2oihqjgfs4ybhxwczaxp5u9fdkmlfu4.png)
Explanation:
The given trigonometric equations are:
![\sin(A+B)=1](https://img.qammunity.org/2022/formulas/mathematics/high-school/jhkgkzzh5yqe6tp7db8lu4pyevg6ih0rn6.png)
![\tan(A-B)=(1)/(√(3))](https://img.qammunity.org/2022/formulas/mathematics/high-school/8fgf4dycdg16ob0luyqhj4pusb7lering5.png)
By referring to the unit circle, we know that sinθ = 1 when θ = π/2. Therefore, we can express the value 1 as sin(π/2):
![\begin{aligned}\sin(A+B)&=1\\\\\sin(A+B)&=\sin \left((\pi)/(2)\right)\\\\A+B&=(\pi)/(2)\end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/high-school/1drr81lw7t57lmi0z3m466c7bbmj2fiv3k.png)
By referring to the unit circle, we find that sinθ/cosθ = 1/√3 when θ = π/6. As a result, we can represent the value 1/√3 as tan(π/6):
![\begin{aligned}\tan(A-B)&=(1)/(√(3))\\\\\tan(A-B)&=\tan \left((\pi)/(6)\right)\\\\A-B&=(\pi)/(6)\end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/high-school/7iq71mc6xe5txa23ks7x1v38zhai7h08wu.png)
Combine the equations to eliminate B, and then solve for A:
![\begin{aligned}A+B+A-B&=(\pi)/(2)+(\pi)/(6)\\\\2A&=(2\pi)/(3)\\\\A&=(\pi)/(3)\end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/high-school/2a8jmeuinfgha89cufonzrdrfqse62kcbz.png)
Substitute the found value of A into the equation for A + B and solve for B:
![\begin{aligned}A+B&=(\pi)/(2)\\\\(\pi)/(3)+B&=(\pi)/(2)\\\\B&=(\pi)/(2)-(\pi)/(3)\\\\B&=(\pi)/(6)\end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/high-school/tngsct9awtymp7w88tzgdbrl7n858wb6j4.png)
Therefore, the values of A and B are:
![A=(\pi)/(3)\qquad B=(\pi)/(6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ojph12ls9xe5qxiqboezs9ntq25ohuy1lp.png)
Now that we have found the values of A and B, we can evaluate the given expressions.
Calculate tan A + tan B:
![\begin{aligned}\tan A + \tan B &=\tan \left((\pi)/(3)\right)+\tan \left((\pi)/(6)\right)\\\\&=√(3)+(√(3))/(3)\\\\&=(3√(3))/(3)+(√(3))/(3)\\\\&=(4√(3))/(3)\end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/high-school/yh9ydl56xabjivqrlf4k54zvt0wasotgvn.png)
Calculate sec A + csc B:
![\begin{aligned}\sec A - \csc B&=(1)/(\cos A)-(1)/(\sin B)\\\\&=(1)/(\cos \left((\pi)/(3)\right))-(1)/(\sin\left((\pi)/(6)\right))\\\\&=(1)/((1)/(2))-(1)/((1)/(2))\\\\&=2-2\\\\&=0\end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/high-school/c2mxju06a55sa2v5f9x7325hazpedr1lw1.png)